Lung transplantation for connective tissue disease–related interstitial lung disease: Clinical outcomes compared to idiopathic pulmonary fibrosis - Sarah L. Khan, MD, MHS; Samuel J. Minkove, MD; Kevin J. Psoter, PhD, MPA; Stephen C. Mathai, MD, MHS; Sonye K. Danoff, MD, PhD; Pali D. Shah, MD (JHLT Open, 2025)
Background: Lung transplantation can be lifesaving for patients with end-stage interstitial lung disease (ILD) related to connective tissue disease (CTD). However, patients with CTD-related ILD (CTD-ILD) are designated as a high-risk group for lung transplant complications due to the potential extrapulmonary manifestations of CTD. Methods: We conducted a retrospective age-matched cohort study of 34 patients with CTD-ILD and 34 patients with idiopathic pulmonary fibrosis (IPF) who underwent lung transplantation between January 2015 and March 2023. The primary outcome was survival free from allograft failure. Secondary outcomes included all-cause mortality and rates of in-hospital surgical complications and acute rejection episodes. Results: Transplant recipients with CTD-ILD and IPF had similar rates of allograft failure and all-cause mortality. However, 3-year all-cause mortality was 5 times higher for transplant recipients with myositis-ILD (incidence rate ratio 5.02, 95% confidence intervals 1.02-24.81). While the rates of in-hospital post-transplant complications and acute rejection were similar for patients with CTD-ILD and IPF, patients with myositis had increased rates of digital ischemia, venous thromboembolism, and infection. Conclusions: Lung transplant recipients with CTD-ILD and IPF had similar rates of allograft failure, all-cause mortality, in-hospital complications, and acute rejection. However, these outcomes varied by CTD diagnosis such that patients with myositis-ILD had increased rates of several in-hospital complications and all-cause mortality. These novel findings provide direction for the ongoing efforts to understand and reduce the risks of lung transplantation for patients with CTD-ILD.